Bioinformatic and Molecular Docking Study of Zerumbone and Its Derivates against Colorectal Cancer - Fauziyya, Riri; Auli, Winni Nur; Suprahman, Nisa Yulianti; Sarmoko, Sarmoko; Ashari, Arif; Alsadila, Kalista; Agustin, Lanita; Fazila, Safia; Zahra, Miralda; Pane, Esteria Christina; Sukrasno, Sukrasno (Indonesian Journal of Cancer Chemoprevention, 2023)
The prevalence of colorectal cancer (CRC) is ranked third among all cancer types in both men and women, highlighting the urgency for drug exploration. Zerumbone and its derivatives have gained attention for their ability to inhibit angiogenesis, invasion, and metastasis and have been tested for their efficacy against various cancer cells. This study aimed to investigate the potential targets and mechanism of action of zerumbone derivatives in colon cancer invasion and migration. Bioinformatic analysis was conducted using STITCH and STRING to identify potential target genes, and molecular docking was used to search for anticancer candidates from 20 zerumbone derivatives. The results revealed that six proteins were targeted by zerumbone derivatives, including XIAPBIR3 (1TFT), AKT1 (3O96), JAK2 (6VGL), HASP90AA (2XJX), MDM2 (4MDN), and XIAPBIR2 (4KJU). Compound 4 was found to have a lower binding energy than zerumbone as well as AZD5363 (pan-Akt inhibitor) when interacting with the protein target AKT1. This makes it the most promising candidate among the zerumbone derivatives for treating colorectal cancer. Further development, such as the addition of an amine functional group, is expected to improve the potency of this molecule through the formation of hydrogen bonds and other interactions with lower bond energy.Keywords: Bioinformatic, molecular docking, zerumbone derivatives, colorectal cancer.